Cerebellar infarction as the initial presentation of IgG4‐related disease. Issue 3 (17th March 2022) - Ireifej, Branden; Dhamrah, Umaima; Song, David; Bitar, Joyce; Jaiswal, Vikash; Nepal, Gaurav; Pathak, Nibesh; Freijat, Majd
Abstract: Although IgG4‐RD has CNS manifestations, cerebellar involvement has only been reported in three cases. Our patient presented with cerebellar symptoms, several cerebellar infarcts were evident on the brain MRI, and CT abdomen revealed retroperitoneal tumor. Endoscopic biopsy confirmed IgG4‐RD. Steroids are the first‐line therapy for IgG4‐RD, but our patient was lost to follow‐up before treatment. Abstract: IgG4‐related disease (IgG4‐RD) is a multiorgan, inflammatory disease with specific histopathological features. This is one of the few cases in which a patient presented with cerebellar symptoms as the initial symptoms for IgG4‐RD.